Analysis of the Existing Community-Level Child Protection Practice in Bosnia and Herzegovina - Softić, Sakib (Kriminalističke teme, 2016)
Reasons for writing and research problem: The purpose of this paper is to show the situation of child protection in Bosnia and Herzegovina most objectively. Aims of the paper (scientific and/or social): The paper is articulated around specific area of interest which includes the systems in place for the delivery of child protection services, related policies and frameworks, child protection education and resources management; data from research of the child protection workforce key skills, knowledge, and interests. Metholodogy / Design: We were used: semi-structured and in-depth interviews and focus group discussions. Field research was done in the period from July to October 2015 in Sarajevo, Banja Luka and Mostar in total, 3 focus groups were organized (1 with students of social work at MA level, 1 with managers/ trainers and 1 with child protection practitioners). Research /paper limitation: Three limitations have been identified in terms of this study. The first limitation is related to the complexity of the system as it is set up in B&H. In addition, the collected data were not collected in an adequate, representative sample. Data were collected during one round of interviews and focus groups with respondents who take up different positions in the system Results / Findings: Findings from the paper will provide a basic analysis f the education and training context in which child protection practices are delivered in Bosnia and Herzegovina and try to identify needs and opportunities for further professional development, training, and/or capacity building to strengthen the child protection workforce in the Bosnia and Herzegovina General conclusion: The results may provide significant insight into processes related to development of the child protection systems in the Bosnia and Herzegovina standardisation of services and quality control mechanisms in terms of human resources development. Research / paper validity: The results should allow a critical analysis of the needs and gaps to be addressed in order to offer appropriate support to professionals from different fields and disciplines in improving the quality of child protection interventions and response.